Coronary artery disease in severe haemophilia. Issue 6 (June 1983) - Small, M; Jack, A S; Lowe, G D; Mutch, A F; Forbes, C D; Prentice, C R
Abstract : It has been suggested that the coagulation defect in haemophilia A protects these patients from coronary artery disease. We report two patients with severe haemophilia, who each had severe atheroma localised to the coronary arteries. Both patients had received only small amounts of factor VIII concentrates in their lifetime because of various social reasons. In one case death resulted from myocardial infarction secondary to an occlusive thrombus in a coronary artery. The implications of these findings to the pathogenesis of vascular disease are discussed.